Information sharing systems and teamwork between sub-teams: a mathematical modeling perspective - Hamid Tohidi; Alireza Namdari; Thomas K. Keyser; Julie Drzymalski (Journal of Industrial Engineering International, 2017)
Teamwork contributes to a considerable improvement in quality and quantity of the ultimate outcome. Collaboration and alliance between team members bring a substantial progress for any business. However, it is imperative to acquire an appropriate team since many factors must be considered in this regard. Team size may represent the effectiveness of a team and it is of paramount importance to determine what the ideal team size exactly should be. In addition, information technology increasingly plays a differentiating role in productivity and adopting appropriate information sharing systems may contribute to improvement in efficiency especially in competitive markets when there are numerous producers that compete with each other. The significance of transmitting information to individuals is inevitable to assure an improvement in team performance. In this paper, a model of teamwork and its organizational structure are presented. Furthermore, a mathematical model is proposed in order to characterize a group of sub-teams according to two criteria: team size and information technology. The effect of information technology on performance of team and sub-teams as well as optimum size of those team and sub-teams from a productivity perspective are studied. Moreover, a quantitative sensitivity analysis is presented in order to analyze the interaction between these two factors through a sharing system.
Keywords: 650; Teamwork; Team size; Sub-team; Information technology; Information sharing system; Productivity